Trends of Antibiotic Resistance in Mesophilic and Psychrotrophic Bacterial Populations during Cold Storage of Raw Milk. (12th March 2012) - Munsch-Alatossava, Patricia; Gauchi, Jean-Pierre; Chamlagain, Bhawani; Alatossava, Tapani
Abstract : Psychrotrophic bacteria in raw milk are most well known for their spoilage potential and cause significant economic losses in the dairy industry. Despite their ability to produce several exoenzyme types at low temperatures, psychrotrophs that dominate the microflora at the time of spoilage are generally considered benign bacteria. It was recently reported that raw milk-spoiling Gram-negative-psychrotrophs frequently carried antibiotic resistance (AR) features. The present study evaluated AR to four antibiotics (ABs) (gentamicin, ceftazidime, levofloxacin, and trimethoprim-sulfamethoxazole) in mesophilic and psychrotrophic bacterial populations recovered from 18 raw milk samples, after four days storage at 4 ∘ C or 6 ∘ C. Robust analysis of variance and non parametric statistics (e.g., REGW and NPS) revealed that AR prevalence among psychrotrophs, for milk samples stored at 4 ∘ C, often equalled the initial levels and equalled or increased during the cold storage at 6 ∘ C, depending on the AB. The study performed at 4 ∘ C with an intermediate sampling point at day 2 suggested that (1) different psychrotrophic communities with varying AR levels dominate over time and (2) that AR (determined from relative amounts) was most prevalent, transiently, after 2-day storage in psychrotrophic or mesophilic populations, most importantly at a stage where total counts were below or around 10 5 CFU/mL, at levels at which the milk is acceptable for industrial dairy industrial processes.